Dermoscopic findings of congenital melanocytic nevus. - Bonifazi, E.; Ciampo, L.; Milano, A.; Argenziano, G. (European Journal of Pediatric Dermatology, 2007)
Congenital melanocytic nevus (CMN) is a nevus present at birth. It consists of epidermal melanocytes and/or dermal nevus cells. In this report the clinical and dermoscopic findings of 326 CMN observed at 10x magnification are reported.